Re-extraction, Recovery, and Characteristics of Skin Gelatin from Farmed Giant Catfish - Sai-Ut,S. (Springer New York, 2015)
This study was aimed to investigate the re-extraction process for gelatin recovery from the skin of farmed giant catfish. The first extraction was done by incubating the acid-treated fish skin at 45 °C for 12 h. The remnant was re-extracted at temperatures of 60-90 °C for 1-12 h. The gelatin yield of the first extraction was 10. 14%, while the re-extraction at high temperature provided higher recovery (19. 5%). Low band intensity of α 1 and α 2 chains of gelatin was observed when it was re-extracted at high temperature for a longer time. The absorption bands of amide I and II from both extracted gelatins were similar. Low-transition temperature with high transition enthalpy of gelatin extracted at 90 °C was observed. The obtained results suggested that the re-extraction process could be applied as a supplemental step for other sources to obtain high recovery with the desired properties. © 2010 Springer Science + Business Media, LLC.